Novel method for mass producing genetically sterile fish from surrogate broodstock via spermatogonial transplantation. Issue 2 (24th September 2018) - Nagasawa, Kazue; Ishida, Mariko; Octavera, Anna; Kusano, Kazunari; Kezuka, Fumi; Kitano, Takeshi; Yoshiura, Yasutoshi; Yoshizaki, Goro
Abstract: A stable system for producing sterile domesticated fish is required to prevent genetic contamination to native populations caused by aquaculture escapees. The objective of this study was to develop a system to mass produce stock for aquaculture that is genetically sterile by surrogate broodstock via spermatogonial transplantation (SGTP). We previously discovered that female medaka carrying mutations on the follicle-stimulating hormone receptor ( fshr ) gene become sterile. In this study, we demonstrated that sterile hybrid recipient females that received spermatogonia isolated from sex-reversed XX males ( fshr (–/–)) recovered their fertility and produced only donor-derived fshr (–) X eggs. Natural mating between these females and fshr (–/–) sex-reversed XX males successfully produced large numbers of sterile fshr (–/–) female offspring. In conclusion, we established a new strategy for efficient mass production of sterile fish. This system can be applied to any aquaculture species for which SGTP and methods for producing sterile recipients can be established. Abstract : Novel method for mass producing genetically sterile fish from surrogate broodstock was established via transplantation of spermatogonia isolated from follicle-stimulating hormone receptor mutants